PREVALENCE OF 2756A>G POLYMORPHISM OF METHIONINE SYNTHASE GENE IN POPULATIONS OF EASTERN SIBERIA - K. D. Ievleva (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
This aim of the study was to research the prevalence of genotypes and alleles of2756A>G polymorphism of gene of methionine synthase (MTR) gene in Russian and Buryat populations of Eastern Siberia. We used DNA blood database of children and teenagers of the Russian and Buryat nationality living in Eastern Siberia. Genotyping was carried out using standard PCR method. Prevalence of minor G-allele in Russian population was 25,7 %, in Buryat population - 13,2 %. We revealed differences in prevalence of genotypes and alleles between studied groups (p = 0,051; p = 0,032).